Leaf traits predict water‐use eficiency in U.S. Pacific Northwest grasslands under rain exclusion treatment - Dawson, Hilary Rose; Maxwell, Toby M.; Reed, Paul B.; Bridgham, Scott D.; Silva, Lucas C. R. (Dryad, 2020)
Does drought stress in temperate grasslands alter the relationship between
plant structure and function? Here we report data from an experiment
focusing on growth form and species traits that affect the critical
functions of water‐ and nutrient‐use efficiency in prairie and pasture
plant communities. A total of 139 individuals of 12 species (11 genera and
four families) were sampled in replicated plots maintained for three years
across a 520-km latitudinal gradient in the Pacific Northwest, USA. Rain
exclusion did not alter the interspecific relationship between foliar
traits and stoichiometry or intrinsic water‐use efficiency (iWUE). Rain
exclusion reduced iWUE in grasses, and effect was primarily
species‐specific, although leaf morphology, life history strategy, and
phylogenetic distance predicted iWUE for all 12 species when analyzed
together. Variation in specific leaf area explained most of the variation
in iWUE between different functional groups, with annual forbs and annual
grasses at opposite ends of the resource‐use spectrum. Our findings are
consistent with expected trait‐driven tradeoffs between productivity and
resource‐use efficiency and provide insight into strategies for the
sustainable use and conservation of temperate grasslands.
Keywords: FOS: Biological sciences; carbon nitrogen ratio; Mean pairwise distance; plant traits; Specific leaf area; Carbon; Climate change; Leaf traits; Pacific Northwest; Plant ecophysiology; intrinsic water-use efficiency; Paleontology; Atmospheric science; Soil science; Water Science and Technology; Ecology; Aquatic Science; Forestry